MENINGKATKAN HASIL BELAJAR IPA MATERI ORGAN GERAK MANUSIA MENGGUNAKAN METODE TANDURDENGAN MEDIA AUDIO-VISUAL PADA MIN 34 ACEH BESAR - Riska Maulida Riska Maulida (Lembaga Sepercenter, 2025)
The low level of student learning outcomes in science lessons is due to a number of students not paying attention and not understanding the teacher's explanations when delivering the material. Some students appear unenthusiastic, and the delivery of material by the teacher is not very interesting because it does not involve the use of media. This study was conducted with the aim of improving student learning outcomes in science lessons on the subject of human movement. Therefore, to achieve this target, it was decided to apply the Tandur method by involving audio-visual media to improve student learning outcomes in studying natural science (IPA) material on the human movement system at the fifth grade level at MIN 34 Aceh Besar. This study is an implementation of classroom action research that utilises specific data collection methods through observation and learning achievement evaluation. A total of 17 students from grade V at MIN 34 Aceh Besar participated in this study. From the data collected in the first and second rounds, there was a recorded increase in student learning outcomes. The percentage of achievement increased from 52.94% in the first period to 85% in the second period